2019
DOI: 10.1111/nmo.13708
|View full text |Cite
|
Sign up to set email alerts
|

Luminal 5‐HT4 receptors—A successful target for prokinetic actions

Abstract: The prokinetic effects of 5‐HT4 receptor (5‐HT4R) agonists have been utilized clinically for almost three decades to relieve symptoms of constipation. Surprisingly, the mechanism(s) of action of these compounds is still being debated. Recent studies highlight luminal 5‐HT4Rs as an alternative and effective target for these prokinetic agents. These include the study by Shokrollahi et al (2019, Neurogastroenterol Motil, e13598) published in the current issue of Neurogastroenterology and Motility, who found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 110 publications
(243 reference statements)
2
23
0
Order By: Relevance
“…37 In conclusion, the concept that activation of luminal 5-HT 4 receptors could provide a safe and effective approach for the treatment of constipation is gaining momentum. 22 The findings described here reveal that novel, luminally acting 5-HT 4 R agonist compounds can generate prokinetic actions in the colon. This further supports effort to selectively target the epithelium within GI tract to generate safe and effective therapies for constipation by avoiding systemic side effects.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…37 In conclusion, the concept that activation of luminal 5-HT 4 receptors could provide a safe and effective approach for the treatment of constipation is gaining momentum. 22 The findings described here reveal that novel, luminally acting 5-HT 4 R agonist compounds can generate prokinetic actions in the colon. This further supports effort to selectively target the epithelium within GI tract to generate safe and effective therapies for constipation by avoiding systemic side effects.…”
Section: Discussionmentioning
confidence: 72%
“…19 Therefore, the concept of targeting luminal 5-HT 4 receptors to alleviate constipation is gaining momentum. 22 In the present study, we tested the hypothesis that 5-HT 4 R agonists that are designed to act within the lumen, with minimal absorption and systemic distribution, could elicit prokinetic actions. In these experiments, we used assays that have been previously described in mice to evaluate the actions of these agents both in vivo and ex vivo, [23][24][25] and we used immunofluorescence to evaluate 5-HT 4 R expression in human intestinal epithelium.…”
Section: -Ht 4 R Agonists Have Prokinetic Actions and As A Result mentioning
confidence: 99%
“…This indicates that 5-HT receptor-mediated mechanisms may play a role in the minute rhythm motor pattern. 5-HT receptors are prominent on enteric neurons ( Keating and Spencer, 2019 ; Spencer and Hu, 2020 ) in the gut mucosa ( Gwynne and Bornstein, 2019 ; Shokrollahi et al, 2019 ) and in the brain ( Browning and Travagli, 2014 ; Browning, 2015 ) and play multiple roles in the physiology and pharmacology of intestinal propulsive motor patterns ( Gershon, 2004 ; Bornstein, 2012 ; Gershon, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the isolated rabbit colon showed that prucalopride could stimulate propulsive contractions when administered directly into the colonic lumen. 50,51 Results from a Phase 3 clinical trial revealed that prucalopride was effective in treating chronic constipation by stimulating at least 3 bowel movements per week. 52 This is relevant to the study by Previous studies used guinea pigs and rats to assess colonic motility and secretion and to test for visceral hypersensitivity.…”
Section: Entero Chromaffin(ec)cellsmentioning
confidence: 99%